Monism in Aristotle’s Metaphysics I.3–5 - Johansen, Thomas Kjeller (Peitho. Examina Antiqua, 2021)
Scholars have often seen Parmenides as entirely opposed to earlier materialistic philosophy. In this paper I argue that what is more striking in Aristotle’s Metaphysics Book I is the degree of continuity that he sees between Parmenides and the material monists. I explore this coupling of Parmenides with the material monists to understand better what he takes to be distinctive and problematic with Parmenides’ monism.